Comparison between Kinesio Taping and a Traditional Physical Therapy Program in Treatment of Nonspecific Low Back Pain - Kachanathu, Shaji John (The Society of Physical Therapy Science, 2014)
[Purpose] Nonspecific low back pain (NSLBP) is a very common but largely self-limiting condition. Several types of tape and their associated application methods are available for different conditions. The aim of the present study was to observe the effect of Kinesio taping (KT) compared with traditional management of NSLBP. [Subjects and Methods] Forty male and female patients with a mean age of 34.8±7.54 years were randomly divided into two groups; group 1 (n=20) which underwent conventional physical therapy with KT, and group 2 (n=20), which underwent only conventional physical therapy. The intervention sessions for both groups were three times per week for four weeks. Outcomes were assessed for activities of daily living (ADL) using the Roland-Morris Disability Questionnaire, pain severity using a visual analogue scale, and ranges of motion (ROMs) of trunk flexion and extension using the modified Schober’s test. [Results] Significant differences in measures of pain, ADL, and trunk flexion and extension ROMs were observed post intervention within each group. In comparison, there were no significant differences in measures of pain, ADL, and trunk flexion and extension ROMs post intervention between groups. [Conclusion] A physical therapy program involving strengthening exercises for abdominal muscles and stretching exercises for back, hamstring, and iliopsoas muscles with or without Kinesio taping was beneficial in the treatment of chronic low back pain.